O processo de ressignificação de crenças e de mudança na prática pedagógica de um professor de inglês em educação continuada - Climene Fernandes Brito Arruda (2008)
This work aims to describe and discuss the process experienced by a teacher of English in the public educational system of the state of Minas Gerais, Brazil, after learning alternative models for his pedagogical practice. This study, developed on a qualitative basis, investigated: a) the teachers own beliefs about his approach to teaching and learning and about evaluation; b) if the teacher resignified his beliefs; c) if changes in the teachers pedagogical practice occured. Data were collected by means of narratives, written and oral; classroom observations; and reflective sessions. The process of analysis was based on questioning the beliefs related to the teachers pedagogical practice. The research shows that the teacher lives significant experiences during his participation in a project of continuing education for foreign language teachers and that he engages in a process of reflection and resignification of beliefs. However, the results reveal that the teacher faces difficulty in making changes in his approach to teaching and learning, but on the other hand, he implements significant changes in his process of evaluation. I conclude the work recommending that studies like this one can help teachers and teacher educators better understand teachers experiences and beliefs, and the processes of change in pedagogical practice.